Using a Health Literacy Analytic Framework to Explore Zika Virus and Reproductive Health - Erika L. Thompson; Cheryl A. Vamos; Langdon G. Liggett; Stacey B. Griner; Ellen M. Daley (SLACK Incorporated, 2018)
Background: The emergence of Zika virus as sexually transmissible and associated with birth defects may affect reproductive planning and contraception use for people in Florida. Objective: This exploratory study employed a health literacy analytic framework to explore knowledge, attitudes, beliefs, and behaviors related to reproductive health in the context of Zika among reproductive-age women and men in Florida. Methods: Reproductive-age people in Florida (N = 40) were interviewed between September and December 2016 about their knowledge, attitudes, beliefs, and behaviors regarding Zika and reproductive health. Thematic analysis using a health literacy framework was employed. Key Results: Participants reported they would use reputable online sources to access Zika information. Whereas participants generally understood Zika outcomes, transmission, and symptoms, they reported hearing more prevention messages on mosquito transmission compared to sexual transmission. Overall, participants reported Zika was not concerning given their appraisal of personal circumstances. Participants were confident they could prevent Zika via sexual transmission despite not following the recommended guidelines. Participants discussed how their understanding of Zika changed their behaviors related to mosquito control but not through sexual transmission. Conclusions: This study illustrated a disconnect between reproductive-age people's understanding of Zika-related prevention information and their reproductive decision-making behavior. Strategies to promote appraisal of risk for sexual transmission of Zika, infection, and unintended pregnancy are needed.